Konsep Pemikiran Tasawuf Akhlaqi - Dwi Muthia Ridha Lubis (Islam & Contemporary Issues, 2021)
Cleaning behavior or cleaning each other's behavior in Sufism is known as akhlaqi. Morals and Sufism are two branches of Islamic knowledge that have been researched and developed by Islamic scholars based on the fundamental concepts of Islam, Al-Quran and Al-Hadith, and reinforced by the Prophet Muhammad's and his companions' deeds. Sunni Sufism is another name for moral Sufism. This Sufi style aims to develop a noble character in the Sufi while avoiding mazmumah (despicable) principles. Humans have the ability to do both good and bad things. Moral Sufism, of course, strives to develop good potential so that humans become good, as well as manage evil potential so that it does not develop into bad action (morals).